Effects of losartan on ventricular remodeling in experimental infarction in rats - Zornoff, Leonardo Antonio Mamede [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP]; Spadaro, Joel [UNESP] (Sociedade Brasileira de Cardiologia (SBC), 2000)
OBJECTIVE: To evaluate the effects of losartan on ventricular remodeling and on survival after myocardial infarction in rats. METHODS: After surgical occlusion of left coronary artery, 84 surviving male Wistar rats were divided into two groups: LO treated with losartan (20mg/kg/day, n=33) and NT (n=51), without medication. After 3 months, we analyzed mortality; ventricular to body mass ratio (VM /BM); myocardial hydroxyproline concentration (HOP); isovolumetric pressure, +dp/dt, -dp/dt, and diastolic volume/left ventricle mass ratio (VO/LV). RESULTS: Mortality was: LO = 22%, and NT = 47% (p<0.05). Ventricular mass,(VM/BM, mg/g) was 4.14 ± 0.76 and 3.54±0.48, in the NT and LO groups, respectively (p<0.05). HOP (median) was 4.92 upsilong/mg in the LO and 5.54 upsilong/g in the NT group (p>0.05). The V0/LV values (median) were 0.24 mL/g in group LO and 0.31 mL/g in group NT (p<0.05) compared to NT group. There were no differences between the groups for +dp/dt and -dp/dt parameters. CONCLUSION: 1- The use of losartan myocardial infarction causes an attenuation of ventricular remodeling, bringing about an increased survival, an attenuation of ventricular hypertrophy and dilation, and an improvement of the isovolumetric pressure; 2- the treatment does not modify the myocardial collagen concentration.
Keywords: fibrosis; ventricular function; angiotensin II